2011
DOI: 10.3354/meps09013
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between pigment ratios and growth irradiance in 11 marine phytoplankton species

Abstract: Light-dependent variation in pigment content was examined in 11 marine phytoplankton species representing 8 algal classes. Batch cultures of each species were acclimated to 7 irradiances between 10 and 700 µmol photons m -2 s -1. High-performance liquid chromatography analysis on exponentially growing cultures revealed that pigment ratios normalised to chlorophyll a (chl a) generally fell within the ranges previously reported for species of the same taxa. Unambiguous lightharvesting pigments (e.g. chlorophylls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 62 publications
4
22
1
Order By: Relevance
“…The pigment ratios, especially the diagnostic pigment ratios for the species isolated from the coast of China are higher than those from other isolations. For example, the Fuco:Tchl a ratio in S. costatum in this study is 1.14 while it is 0.143 in Llewellyn and Gibb (2000) (CCAP-1077/5) and 0.384 in Laviale and Neveux (2011) (RCC-70), respectively. However, the Fuco/Tchl a ratio in S. costatum in this study was very close to that in the same species with the same isolation reported by Yao et al (2006) (1.171).…”
Section: Pigment Ratiosmentioning
confidence: 78%
“…The pigment ratios, especially the diagnostic pigment ratios for the species isolated from the coast of China are higher than those from other isolations. For example, the Fuco:Tchl a ratio in S. costatum in this study is 1.14 while it is 0.143 in Llewellyn and Gibb (2000) (CCAP-1077/5) and 0.384 in Laviale and Neveux (2011) (RCC-70), respectively. However, the Fuco/Tchl a ratio in S. costatum in this study was very close to that in the same species with the same isolation reported by Yao et al (2006) (1.171).…”
Section: Pigment Ratiosmentioning
confidence: 78%
“…Xanthophyll pigments, such as DD and DT, are present in Prymnesiophyceae, Dinophyceae and Bacillariophyceae (Silva et al, 2007;Laviale and Neveux, 2011), and are thought to infl uence the spatial distribution of these organisms, as does the WSC in the inner bay. The Cryptophyte Rhodomonas baltica does not produce DT or DD but is known to utilize alloxanthin as a xanthophyll pigment (Laviale and Neveux, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to optically identify A. tamarense, further studies are needed to investigate the absorption and reflectance due to MAAs, as in the investigation of Kahru and Mitchell (1998). The pigment composition of phytoplankton varies widely with changes in irradiance (Laviale & Neveux, 2011) and micro-and macronutrients (Hopkinson et al, 2007). The absorption spectra of phytoplankton were also influenced by the package effect (Morel & Bricaud, 1981), cell-size composition (Ciotti et al, 2002), photoacclimation (Staehr & Cullen, 2003), and changes in light (Johnsen & Sakshaug, 2007).…”
Section: Tablementioning
confidence: 96%